Determination of Tetracycline Residues in Kidney and Muscle of Beef Cattle Slaughtered in Dire Dawa and Harar Municipal Abattoirs, Eastern Ethiopia. (July 2022) - Mohammed, Nuredin; Adare Mengistu, Dechasa; Abdurehman, Abdallahi; Belina, Dinaol; Mengistu, Shimelis
Background: Antibiotics are among the most widely used drugs in farm animals for therapeutic and prophylactic purposes. However, the antibiotic residues in meat are a serious public health concern due to their harmful effects on consumer health. Besides this problem, there is limited information on the level of the antibiotic residues, including tetracycline residues. Therefore, this study was aimed to determine the tetracycline residues in the kidney and muscle samples of beef cattle in Harar town and Dire Dawa city. Methods: A study was conducted on 500 randomly selected carcass (250 kidney and 250 muscle samples) slaughtered at Dire Dawa and Harar municipal slaughterhouses between December 2018 and December 2019. The samples were collected aseptically and screened for tetracycline residues by thin layer chromatography. Then, presumptive positive samples were analyzed using high-performance liquid chromatography to get a quantitative outcome. Descriptive statistics were used to determine the frequency, mean, or standard deviation to determine the summary values and distribution of the outcomes. Finally, the data was analyzed using SPSS version 21 software. Results: Out of 500 samples, oxytetracycline residues were detected in 84% of the samples. However, tetracycline and doxycycline were not detected in all samples. Among the kidney and muscle samples collected from Dire Dawa and Harar abattoirs, 109 (87.2%) and 101 (80.8%) were positive for oxytetracycline, respectively. Oxytetracycline residue levels in Dire Dawa ranged from 57 to 607 µg/kg for the kidney and 10.14 to 435 µg/kg for muscle samples. Among the samples collected from Harar, the concentration of oxytetracycline residues ranged from 16 to 433 µg/kg and 6 to 435 µg/kg for kidney and muscle samples, respectively, at Harar slaughterhouses. About 22.0% of muscle samples collected from Dire Dawa and 17.8% from Harar town had oxytetracycline residues above maximum residue limits. Conclusions: In general, the study revealed that oxytetracycline residues were prevalent among tetracycline residues analyzed from kidney and muscle samples in the study areas. Thus, there is a risk of consumer exposure to these antibiotic residues that may have human health effects. Therefore, awareness creation and strict regulation is needed by the regulatory authorities for the use of antimicrobial drugs in the livestock industry.